2017
DOI: 10.1111/bjd.14843
|View full text |Cite
|
Sign up to set email alerts
|

Safety, complications and patients’ acceptance of Mohs micrographic surgery under local anaesthesia: results from the U.K. MAPS (Mohs Acceptance and Patient Safety) Collaboration Group

Abstract: Mohs micrographic surgery (MMS) is recognized as the goldstandard treatment for high-risk nonmelanoma skin cancers (NMSC) of the head and neck. Given the rising incidence of skin cancer, the past two decades have seen a rapid increase in the number of centres providing this service in the U.K. However, data on the safety, complication rates and patient acceptance of MMS in the U.K. are lacking. Over a 3-month period (September to November 2012) eight regional MMS centres collected data that included tumour sit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
20
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 12 publications
3
20
0
2
Order By: Relevance
“…Our study shows that the rate of complications is low but more frequent when treating SCC than BCC. As previously reported, we have found that perioperative bleeding is the most common adverse event …”
Section: Discussionsupporting
confidence: 71%
See 2 more Smart Citations
“…Our study shows that the rate of complications is low but more frequent when treating SCC than BCC. As previously reported, we have found that perioperative bleeding is the most common adverse event …”
Section: Discussionsupporting
confidence: 71%
“…Mohs micrographic surgery is a very safe procedure with a very low rate of perioperative adverse events. Most of the complications are minor, such as bleeding, site infection, and end‐skin necrosis/dehiscence, which are the most common complications described . Our study shows that the rate of complications is low but more frequent when treating SCC than BCC.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…Nuestros registros muestran una prevalencia de CBC por sobre CEC; sin embargo, encontramos una cantidad de CEC superior a la esperada (32%) al comparar con otros estudios similares (3,54% -5,64%) (11,(13)(14)(15) . En cuanto a los tipos histopatológicos de los carcinomas, Leibovitch y colaboradores reportan que los subtipos histopatológicos más frecuentes de CBC fueron el infiltrante con 30,7%, luego el nódulo-quístico con 24,2% y el superficial con 13,6% (10) .…”
Section: Tamaño De Los Defectos Quirúrgicos Finalesunclassified
“…Hussain y colaboradores reportan una incidencia de complicaciones menores de 7,78% en sus CMM, las cuales fueron de características similares a las vistas en nuestros pacientes (15) . El seguimiento al año de la cirugía fue completado en 54%, con un tiempo promedio de 386 días (rango: 9 días a 40 meses).…”
Section: Tamaño De Los Defectos Quirúrgicos Finalesunclassified